A dynamic multi-objective evolutionary algorithm with variable stepsize and dual prediction strategies - Peng, Hu; Pi, Chen; Xiong, Jianpeng; Fan, Debin; Shen, Fanfan (Future generation computer systems, 2024)
The prediction strategy is a key method for solving dynamic multi-objective optimization problems (DMOPs), particularly the commonly used linear prediction strategy, which has an advantage in solving problems with regular changes. However, using the linear prediction strategy may have limited advantages in addressing problems with complex changes, as it may result in the loss of population diversity. To tackle this issue, this paper proposes a dynamic multi-objective optimization algorithm with variable stepsize and dual prediction strategies (VSDPS), which aims to maintain population diversity while making predictions. When an environmental change is detected, the variable stepsize is first calculated. The stepsize of the nondominated solutions is expressed by the centroid of the population, while the stepsize of the dominated solutions is determined by the centroids of the clustered subpopulations. Then, the dual prediction strategies combine an improved linear prediction strategy with a dynamic particle swarm prediction strategy to track the new Pareto-optimal front (PF) or Pareto-optimal set (PS). The improved linear prediction strategy aims to enhance the convergence of the population, while the dynamic particle swarm prediction strategy focuses on preserving the diversity of the population. There have also been some improvements made in the static optimization phase, which are advantageous for both population convergence and diversity. VSDPS is compared with six state-of-the-art dynamic multi-objective evolutionary algorithms (DMOEAs) on 28 test instances. The experimental results demonstrate that VSDPS outperforms the compared algorithms in most instances. •Using the linear prediction strategy only may result in the loss of population diversity.•A dynamic particle swarm prediction strategy is used to increase the population diversity.•An improved linear prediction strategy is used to improve the population convergence.•Nondominated and dominated solutions have different stepsizes when making predictions.•Dual prediction strategies are proposed to predict the population at next time.